2015
DOI: 10.1007/s11104-015-2553-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of historical logging on soil microbial communities in a subtropical forest in southern China

Abstract: Background and Aims Gaining a better understanding of the legacy effects of logging and forest restoration on soil microbial communities could improve our ability to conserve biodiversity and promote ecosystem sustainability. Herein, we investigated how soil microbial community is linked to natural, restored, and planted forests and the legacies of historical forest. Methods Soil microbial biomass and composition were measured in four forest types (i.e., primary forest, onceclearcut forest, twice-logged forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 54 publications
(56 reference statements)
1
17
0
1
Order By: Relevance
“…However, when the forest matured further, the canopy of the forests became denser, which reduced forest floor light and slowed decomposition of litter. Vegetations such as shrubs and herbs also declined consequently, which decreased soil nutrients and together lead to slower microbial growth (Kaiser et al 2011;Song et al 2015).…”
Section: Difference In the Soil Microbial Biomass Of Different Forestsmentioning
confidence: 99%
“…However, when the forest matured further, the canopy of the forests became denser, which reduced forest floor light and slowed decomposition of litter. Vegetations such as shrubs and herbs also declined consequently, which decreased soil nutrients and together lead to slower microbial growth (Kaiser et al 2011;Song et al 2015).…”
Section: Difference In the Soil Microbial Biomass Of Different Forestsmentioning
confidence: 99%
“…3, 6). Severer C limitation in urban forests than suburban forests may cause the reduction of soil microbial biomass 34,55 . A large proportion of plant material is transformed from soil microorganisms into soil C on the one hand and 56 , on the other hand, microbial products contribute greatly to stable C 25,57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the vegetation community, nitrogen cycle, soil C pool, soil uptake potential for greenhouse gases, soil heavy metal pollution, soil microbes, etc. in urban remnant forests of the southern subtropical monsoon climate zone have changed in the highly-urbanized Pearl River Delta (PRD) region 6,[30][31][32][33][34][35] . When studying Pinus massoniana forests in South China, Chen et al 30 indicated that the soil C pools were lower in urban sites because of the significant decrease in fine root biomass and a potential increase in SOC decomposition.…”
mentioning
confidence: 99%
“…Land-use type and management can be primary factors that directly affect soil microbial communities or can indirectly affect communities through biotic and abiotic factors (Courtney, Harris, & Pawlett, 2014;Li et al, 2018;Nakayama et al, 2019;Tripathi et al, 2016;Xue et al, 2017;Yang et al, 2019). As major anthropogenic disturbances, such as selective logging can definitively affect ecosystem multifunctionality (Delgado-Baquerizo et al, 2016;Lee-Cruz, Edwards, Tripathi, & Adams, 2013;Song, Ren, Jia, Guo, & Zhang, 2015), the effects of such practices on the microbial community require more attentions for effective forest management. Although selective logging is defined as a "sustainable forest management" (Rist et al, 2012), the impact of selective logging on ecosystem functions requires further investigation, particularly in relation to the degradation and increasing atmospheric CO 2 levels (Gatti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%